AN ANALYSIS OF USING CODE SWITCHING IN INSTAGRAM - Kamariah Kamariah; Ambalegin Ambalegin (BASIS (Bahasa dan Sastra Inggris), 2019)
The phenomenon of code switching nowadays is very often encountered in both direct and indirect communication or on social media. This research aims to describe the forms and the factors of using code switching that using in on Instagram. After doing the analysis researcher consider there are three kinds of form code switching that found on instagram account using by instagram users they are: tag-switching, intersentential code switching, and intrasetential code switching. Then after doing the analysis based on of the types, researcher founds the reasons of using code switching there are four points: changing topic, lack of vocabulary, bilingual/multilingual, Prestige and trend. This research using sociolinguistic study because it’s related to the topic in this research. Then the researcher used qualitative research methods in doing the analysis. This research are expected to be useful in the process of learning language, especially studies of sociolinguistic and the using of language.